Pengaruh Perlakuan Permukaan Pengikatan Terhadap Sifat Mekanik Komposit Serat Kaca Dengan Laminasi Almunium - Muhammad Fakhruddin; Maskuri Maskuri; Elka Faizal; Bayu Pranoto; Hangga Wicaksono; Hilmi Iman Firmansyah (Jurnal Energi dan Teknologi Manufaktur, 2021)
Fiber metal laminates or commonly known as fiber metal laminates (FML) are composite structures made by combining 2 layers of material as the outer layer with the core material. The outer layer of this composite is called the laminate. Generally, laminated composites are produced by joining techniques under solid-state conditions, such as diffusion bonding, extrusion, friction-stir welding, and roller welding. In this study, glass fiber composites with aluminum lamination were made using the vacuum assisted resin infusion (VARI) method, using epoxy resin. The surface treatment of the aluminum laminate was carried out with the direction of roughing at certain angles and variations of the surface roughening of the laminate to test the mechanical bonding between the composite and the laminate. Mechanical bonding testing using three-point bending test method (three-point bending) and buckling test. The expected result is that by surface treatment on aluminum laminate, the best mechanical bonding to composites with glass fiber is obtained. The TKT to be achieved from this research is TKT level 3, which is an analytical study that supports the prediction of the performance of the effect of the bonding surface treatment on the mechanical properties of glass fiber composites with aluminum lamination.